2022
DOI: 10.1039/d1sc06554h
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing thermal quenching of lead halide perovskite nanocrystals by constructing a wide-bandgap surface layer for achieving thermally stable white light-emitting diodes

Abstract: Lead halide perovskite nanocrystals as promising ultrapure emitters are outstanding candidates for the next-generation light-emitting diodes (LED) and display applications, but the thermal quenching behavior of light emission has severely...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Recently, we demonstrated stable CsPbBr 3 QDs-SiO 2 ceramic particles produced via solid-state NCs growth using mesoporous silica templates, which combine the excellent optical properties of perovskite NCs in one of the most stable nanomaterials available to date. Other research groups also demonstrated that high-quality CsPbX 3 NCs can be synthesized in host matrixes, such as metal–organic frameworks (MOFs), glasses, and metal oxides. Although successful in protecting the QDs from the environment, all these approaches, including ours, produce overly large particles (>2 μm) or even bulk glasses, which makes them unsuitable for uniform embedding into tiny μ-LED chips. , Therefore, all currently available color conversion materials, including conventional ceramic phosphors (too large size), conventional or perovskite NCs (unstable), and perovskite composites and glasses (too large size), cannot simultaneously fulfill the optical, stability, and particle size requirements for successful applications in μ-LEDs.…”
Section: Synthesis and Properties Of Cspbbr3 Ncs Inside Msnsmentioning
confidence: 99%
“…Recently, we demonstrated stable CsPbBr 3 QDs-SiO 2 ceramic particles produced via solid-state NCs growth using mesoporous silica templates, which combine the excellent optical properties of perovskite NCs in one of the most stable nanomaterials available to date. Other research groups also demonstrated that high-quality CsPbX 3 NCs can be synthesized in host matrixes, such as metal–organic frameworks (MOFs), glasses, and metal oxides. Although successful in protecting the QDs from the environment, all these approaches, including ours, produce overly large particles (>2 μm) or even bulk glasses, which makes them unsuitable for uniform embedding into tiny μ-LED chips. , Therefore, all currently available color conversion materials, including conventional ceramic phosphors (too large size), conventional or perovskite NCs (unstable), and perovskite composites and glasses (too large size), cannot simultaneously fulfill the optical, stability, and particle size requirements for successful applications in μ-LEDs.…”
Section: Synthesis and Properties Of Cspbbr3 Ncs Inside Msnsmentioning
confidence: 99%
“…[6][7][8] More importantly, the stabilities problem that restricted the development of Pb-based perovskite have also been greatly improved by encapsulation, extending from the initial life of a few hours to hundreds of hours. [9][10][11][12] However, the highly intrinsic toxicity of heavy metal Pb causes a potential threat to the environment and human health, which seriously hinders their practical application. [13,14] Therefore, there is considerable interest in trying to replace Pb with non-toxic or less toxic elements, for example, isovalent substitution (Sn 2 + , Ge 2 + ) or heterovalent substitution (Bi 3 + , Ag + ), to form lead-free perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent CsPbX 3 have made rapid developments, such as nearly unity PLQY and high‐efficient light‐emitting diodes (LED) devices with external quantum efficiencies exceeding 20 % [6–8] . More importantly, the stabilities problem that restricted the development of Pb‐based perovskite have also been greatly improved by encapsulation, extending from the initial life of a few hours to hundreds of hours [9–12] . However, the highly intrinsic toxicity of heavy metal Pb causes a potential threat to the environment and human health, which seriously hinders their practical application [13, 14] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Inspired by nature, many scientists have begun to pay attention to the development of articial light-harvesting systems (ALHSs), [4][5][6][7] which have promoted the remarkable development in optoelectronic and photonic materials and devices such as photocatalysis, 7-10 solar cells, [11][12][13][14] optical sensors, [15][16][17][18] and luminescent materials. [19][20][21][22] However, most of the reported sophisticated ALHSs are manufactured in organic solvents rather than in aqueous media as in nature, which hinders their actual applications. Due to the limitations of the solubility of hydrophobic chromophores in water and the quenching effect caused by undesirable aggregation, ALHSs constructed in an aqueous environment usually show unsatisfactory performance.…”
Section: Introductionmentioning
confidence: 99%